2020
DOI: 10.3201/eid2610.20211
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Responses to SARS-CoV-2 at 8 Weeks Postinfection in Asymptomatic Patients

Abstract: RESEARCH LETTERS We compared levels of severe acute respiratory syndrome coronavirus 2 neutralizing antibodies in recovery plasma from 7 completely asymptomatic coronavirus disease patients with those in symptomatic patients in South Korea. We found that serologic diagnostic testing was positive for 71% (5/7) of completely asymptomatic patients, but neutralizing antibody response occurred in all 7 patients. as informing the public about food shortage while reassuring the public that supply will arrive in a few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
32
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 6 publications
10
32
1
Order By: Relevance
“…Through campus screening efforts, we also identified 6 PCR+ individuals who either never developed symptoms or had only a brief and mild headache or anosmia. Although previous reports suggested that such individuals may infrequently seroconvert or frequently serorevert (Long et al, 2020a;Sekine et al, 2020), all such individuals in our cohort showed seroreactivity to RBD, S2, and all but one to N (Figures S3A-C), consistent with other recent studies (Choe et al;Ko et al, 2020). Given that older adults, as well as those of male sex, exhibit disproportional morbidity and mortality from COVID-19, we also sought to test whether humoral immunity in these subjects may be quantitatively reduced (Liu et al, 2020).…”
Section: Resultssupporting
confidence: 92%
“…Through campus screening efforts, we also identified 6 PCR+ individuals who either never developed symptoms or had only a brief and mild headache or anosmia. Although previous reports suggested that such individuals may infrequently seroconvert or frequently serorevert (Long et al, 2020a;Sekine et al, 2020), all such individuals in our cohort showed seroreactivity to RBD, S2, and all but one to N (Figures S3A-C), consistent with other recent studies (Choe et al;Ko et al, 2020). Given that older adults, as well as those of male sex, exhibit disproportional morbidity and mortality from COVID-19, we also sought to test whether humoral immunity in these subjects may be quantitatively reduced (Liu et al, 2020).…”
Section: Resultssupporting
confidence: 92%
“…3b) and in a larger cohort of individuals screened for serum antibodies within our health system 25 . Others have reported similar findings [26][27][28] . We did not observe a correlation between donor serum neutralizing titers and convalescent plasma-recipient outcomes (Fig.…”
Section: Nature Medicinesupporting
confidence: 66%
“…Their increased and possibly continued presence in severely ill patients underscores the nature of this humoral response as an "emergency supply system," ensuring the rapid production of protective Abs, both switched and nonswitched. Asymptomatic patients and those with mild disease exhibit lower overall Ab responses but do also possess neutralizing titers (33)(34)(35). As convalescence begins, B cell responses shift from "emergency supply" to the development of long-lived responses in germinal center responses, which are geared toward developing protection from future re-encounters.…”
Section: Fundamentals Of B Cell Responses To Acute Viral Infectionsmentioning
confidence: 99%